Shadow banks and the risk-taking channel of monetary policy: Transmission in the euro area - Arina Wischnewsky; Matthias Neuenkirch (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2018)
In this paper, we provide evidence for a risk-taking channel of monetary policy transmission in the euro area that works through an increase in shadow banks' total asset growth and their risk assets ratio. Our dataset covers the period 2003Q1 - 2017Q3 and includes, in addition to the standard variables for real GDP growth, inflation, and the monetary policy stance, the aforementioned two indicators for the shadow banking sector. Based on vector autoregressive models for the euro area as a whole, we find for conventional monetary policy shocks that a portfolio reallocation effect towards riskier assets is more pronounced, whereas for unconventional monetary policy shocks we detect stronger evidence for a general expansion of assets. Country-specific estimations confirm these findings for most of the euro area countries, but also reveal some heterogeneity in the shadow banks' reaction.
Keywords: E44; E52; E58; G11; G23; G28; 330; European Central Bank; Macroprudential Policy; Monetary Policy Transmission; Risk-Taking Channel; Shadow Banks; Vector Autoregression